Dashboard Prestasi Siswa SMPN 1 Purwakarta: Visualisasi Data dengan Google Looker Studio - Fakhirah Azhar; Nuur Wachid Abdulmajid; Beni Ari Hidayatullah (Progresif: Jurnal Ilmiah Komputer, 2025)
Management of non-academic student achievement data, which has been presented in various formats, is difficult to analyze systematically. This research aims to develop a visual dashboard of student achievement based on Google Looker Studio at SMPN 1 Purwakarta. The research uses the CRISP-DM (Cross Industry Standard Process for Data Mining) method which consists of six stages, namely business understanding, data understanding, data preparation, modeling, evaluation and deployment. The data used includes exam results and student participation in various competitions. Dashboards were developed to present information visually, interactively and in real-time to support data-based evaluation and decision making. The development results show that this dashboard is able to integrate student achievement data into one platform that is easy to access and understand by teachers and school officials. The conclusion of this research is that the use of a dashboard based on Google Looker Studio can make a significant contribution to improving the quality of managers.Keywords: Dashboard; Student Achievement; Data Visualization; Google Looker Studio AbstrakPengelolaan data prestasi siswa non-akademik yang selama ini disajikan dalam berbagai format, sulit dianalisis secara sistematis. Penelitian ini bertujuan untuk mengembangkan dashboard visual prestasi siswa berbasis Google Looker Studio di SMPN 1 Purwakarta. Penelitian menggunakan metode CRISP-DM (Cross Industry Standard Process for Data Mining) yang terdiri dari enam tahapan, yaitu business understanding, data understanding, data preparation, modeling, evaluation, dan deployment. Data yang digunakan mencakup hasil ujian dan keikutsertaan siswa dalam berbagai lomba. Dashboard dikembangkan untuk menyajikan informasi secara visual, interaktif, dan real-time guna mendukung evaluasi dan pengambilan keputusan berbasis data. Hasil pengembangan menunjukkan bahwa dashboard ini mampu mengintegrasikan data prestasi siswa ke dalam satu platform yang mudah diakses dan dipahami oleh guru maupun pihak sekolah. Kesimpulan dari penelitian ini adalah bahwa penggunaan dashboard berbasis Google Looker Studio dapat memberikan kontribusi yang signifikan dalam meningkatkan kualitas pengelola.Kata kunci: Dashboard; Prestasi Siswa; Visualisasi Data, Google Looker Studio